+0  
 
+1
371
2
avatar+154 

Thank Ya

 Dec 7, 2017

Best Answer 

 #1
avatar+7352 
+2

C   =   2π * r          Divide both sides of the equation by  2π

C / ( 2π )   =   r

 

y   =   -\(\frac14\)x + 3         Multiply every term in this equation by  4 .

4y   =   -x + 12        Add  x  to both sides of the equation.

x + 4y   =   12

 

2x + 3y   =   9            Subtract  2x  from both sides of this equation.

3y   =   -2x + 9           Divide every term in this equation by  3 .

y   =   -\(\frac23\)x + 3

 

4x - 3y   =   -18         To find the y-intercept, plug in  0  for  x  and solve for  y .

4(0) - 3y   =   -18

-3y   =   -18

y   =   6                      So the y-intercept is  6 .

 

y   =   \(\frac12\)x + 6        To find the x-intercept, plug in  0  for y  and solve for  x .

0   =   \(\frac12\)x + 6

-6   =   \(\frac12\)x

-12   =   x              So the x-intercept is  -12 .

 Dec 7, 2017
 #1
avatar+7352 
+2
Best Answer

C   =   2π * r          Divide both sides of the equation by  2π

C / ( 2π )   =   r

 

y   =   -\(\frac14\)x + 3         Multiply every term in this equation by  4 .

4y   =   -x + 12        Add  x  to both sides of the equation.

x + 4y   =   12

 

2x + 3y   =   9            Subtract  2x  from both sides of this equation.

3y   =   -2x + 9           Divide every term in this equation by  3 .

y   =   -\(\frac23\)x + 3

 

4x - 3y   =   -18         To find the y-intercept, plug in  0  for  x  and solve for  y .

4(0) - 3y   =   -18

-3y   =   -18

y   =   6                      So the y-intercept is  6 .

 

y   =   \(\frac12\)x + 6        To find the x-intercept, plug in  0  for y  and solve for  x .

0   =   \(\frac12\)x + 6

-6   =   \(\frac12\)x

-12   =   x              So the x-intercept is  -12 .

hectictar Dec 7, 2017
 #2
avatar+154 
+1

Thanks somuch

 Dec 9, 2017

23 Online Users

avatar
avatar
avatar
avatar